STEROLS PRESENT IN THE APOLAR EXTRACT OF GARLIC ROOTS OF GARLIC SACHA Mansoa alliacea - Grovas Llamocca, Jenny E. (2018)
From the apolar extract of the roots of garlic Sacha Mansoa alliacea collected in the Botanical garden of Center of Rehabilitation of addictions and research of traditional medicines – Takiwasi (Tarapoto, San Martin region, in the Peruvian Amazon) identified stigmasterol (90,36 %) and γ-sitosterol (8,76 %) as their main sterols, wich were analyzed by gas chromatography and identified by their mass spectra. In addition, was the qualitative analisys of the secondary metabolites.